A new record of late Pliocene-early Pleistocene aeolian loess–red clay deposits from the western Chinese Loess Plateau and its palaeoenvironmental implications. (15th April 2018) - Zan, Jinbo; Fang, Xiaomin; Zhang, Weilin; Yan, Maodu; Zhang, Dawen
Abstract: The loess–red clay sequences in northern China provide high-resolution terrestrial records of Asian monsoon evolution and aridification of the Asian interior. To date, however, aeolian deposits of late Pliocene-early Pleistocene age (3.5–2.4 Ma) have only rarely been reported from the western Chinese Loess Plateau (CLP), which significantly hinders our understanding of the distribution of aeolian deposits and the palaeoenvironmental evolution of the region. Here, we present magnetostratigraphic, lithologic and magnetic susceptibility results for two recently-drilled boreholes from the north bank of Baxie River, central Linxia Basin, which are highly correlative with those of the loess–red clay deposits spanning the interval from 3.6 to 2.4 Ma in the eastern CLP. Our results provide the first direct evidence for the occurrence of late Pliocene-early Pleistocene aeolian deposits in the western CLP and provide new insights into the distribution of aeolian deposits in northern China. The spatial coherence of the magnetic susceptibility fluctuations further indicates that magnetic susceptibility is a powerful tool for stratigraphic correlation of late Pliocene aeolian deposits in the western CLP. In addition, our results demonstrate that erosional events may have occurred in the early or middle Pleistocene, and they may provide new insights into the reasons for the absence of loess–red clay deposits from 3.5 to 2.4 Ma in most parts of the western CLP. Highlights: Identification of the 3.6–2.4 Ma loess–red clay deposits in the western CLP. Synchronous changes in magnetic susceptibility between the western and eastern CLP. New clues into the reasons for the absence of Pliocene aeolian deposits in the western CLP.